The Global Trend towards Intensification: What About Welfare? - Amores, Mária José (Spei Domus, 2014)
In today’s world, food production is facing major challenges: a consumer market that is growing relentlessly, diversifying consumer tastes, and an increase in areas of biofuel production, which competes with food production. This is combined with an accelerating rate of deforestation in sensitive zones and an indiscriminate increase in methane emissions (both direct and indirect) into the atmosphere, water and soil, from agriculture in general. And finally, there is an increasingly greater gap between those who can afford quality food those who can barely manage one meal a day with low nutritional content. In this global situation, there is a trade off between animal production and welfare and the challenge of mass-producing food by means of intensification and the use of grain-rich diets, partial or total confinement, and specialized genetics to increase production. This, however, translates into ruminal acidosis, high incidence of lameness, and problems with behavior and adaptation. The aim of this article is to conduct a general review of the agricultural production panorama, especially that of cattle in Ecuador, from economic, social, environmental and animal welfare perspectives, bearing in mind that the changes in any production system take place in response to the consumer; ultimately, it is the consumer who should be addressed to achieve an ethical food supply that is socially responsible, environmentally sustainable, and consistent with animal welfare.